Perceptual drifts of real and artificial limbs in the rubber hand illusion - Fuchs, Xaver; Flor, Herta (Scientific reports, 2016)
In the rubber hand illusion (RHI), transient embodiment of an artificial hand is induced. An often-used indicator for this effect is the “proprioceptive drift”, a localization bias of the real hand towards the artificial hand. This measure suggests that the real hand is attracted by the artificial hand. Principles of multisensory integration, however, rather suggest that conflicting sensory information is combined in a “compromise” fashion and that hands should rather be attracted towards each other. Here, we used a new variant of the RHI paradigm in which participants pointed at the artificial hand. Our results indicate that the perceived positions of the real and artificial hand converge towards each other: in addition to the well-known drift of the real hand towards the artificial hand, we also found an opposite drift of the artificial hand towards the real hand. Our results contradict the notion of perceptual substitution of the real hand by the artificial hand. Rather, they are in line with the view that vision and proprioception are fused into an intermediate percept. This is further evidence that the perception of our body is a flexible multisensory construction that is based on integration principles.
Gesehen am 04.04.2019